Strong-field approximation for analytical calculation of the residual current density excited by gas ionization with an intense two-color laser pulse - Romanov, A.A.; Silaev, A.A.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2015)
On the basis of analytical solution of the time-dependent Schrödinger equation the excitation of residual current density (RCD) in a gas ionized by two-color laser pulse is studied. We find general analytical expression for the RCD for arbitrary values of the Keldysh parameter, which coincides with the semiclassical calculations in the case of tunneling regime of ionization.